Characterization of the Sensory Processing of Infants Assisted in an Early Stimulation Program (Research, Society and Development, 2020)
Objectives: To characterize sensory processing of children with neuropsychomotor developmental delay assisted in an Early Stimulation Program. Methodology: Quantitative, descriptive, analytical and cross-sectional study conducted at a referral hospital in Pernambuco. 24 caregivers of children aged 0 to 35 months who were being attended by the service participated in this study. For the group up to 6 months, the Sensory Profile 2 of the baby instrument was used and for the group above 7 months, the Sensory Profile 2 of the Child of practical applicability. Results: Most children in the group up to 6 months presented unexpected performance (hyperresponsiveness) for sensory processing patterns. In the group of children older than 7 months, expected performance was observed for most in the quadrants and sensory sections (general, auditory, touch and oral) except for the visual, movement and behavioral sensory sections (hyperresponsiveness and hyporesponsiveness). Conclusion: Children with neuropsychomotor developmental delays showed different responses to sensory processing patterns, whether more (hyperresponsiveness) or less (hyporesponsiveness), and follow-up with the multidisciplinary team is recommended to plan strategies that address the responses that most affect Your participation.